A Study on Internet and Gaming Addiction, Hikikomori Trait and Insomnia Status among Medical Undergraduates at one of Cities of Western India - Solanki, Sahil R; Shukla, Rujul Pankajbhai; Dave, Viral R; Rathod, Vasu G (Indian Journal of Community Health, 2023)
Background: College students appear more vulnerable in developing a dependence on the internet. Individuals with hikikomori are frequently reported to have social contact predominantly via the internet. Objectives: To find the prevalence of Internet addiction, gaming Addiction, Hikikomori Trait and Insomnia amongst medical undergraduates and to study their association with various determinants. Methodology: The present Cross-Sectional study was conducted among first to final-year medical students studying at various medical colleges in Indian City from February to May 2021. Data collection was done after obtaining the ethical permission of the Institute. A total of 400 students who gave consent were sent an electronic questionnaire. Results: The mean age of study participants was 20 ± 1.58 years. Internet addiction was present in 189(47.2%) participants, gaming addiction in 128 (32%) students and Hikikomori Trait was found in 98(24.5%) students. There was a statistically significant association between different grades of insomnia and internet, gaming addiction, and hikikomori trait (<?0.0001) in the present study. Conclusion: Internet addiction was present in almost half of the medical students while gaming addiction was seen in nearly one third of the students. Male gender and hostel stay had a statistically significant association with internet addiction, gaming addiction, insomnia and hikikomori trait.